EVALUATION OF CHARACTERISTICS OF RESISTANCE OF PROPAGATION OF CORROSION- FATIGUE CRACKS OF LONG-TERM OPERATED DRILL PIPES - Vytyaz, О. Yu.; Hrabovskyi, R. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
The aim of the proposed article is to determine the patterns of the corrosion-fatigue cracks in long-term operational metal elements of drill strings (steel 45, 36G2S, 40HN) when drilling wells in corrosive environments (drilling fluid "Biocar", potassium polymer mud and on the air). Based on the obtained results of experimental studies, diagrams of cyclic corrosion crack resistance for the studied systems "metal - medium" were drawn. The cyclic crack resistance characteristics of long-used metals of drill string elements are determined - the values of constants (C and n) in power dependence of Paris, as well as the values of threshold and critical stress intensity factory. The influence of drilling mud of the corrosion crack resistance of the investigated metals of drill string elements was estimated quantitatively. In particular, in the environment of drilling mud "Biocar" the process of corrosion-fatigue crack development in the studied metals of the elements of drill strings is not significantly, in the range of 1-5%, differs from the development of fatigue crack on the air. Whereas in the potassium polymer drilling mud media, the rate of corrosion-fatigue cracks development in the investigated metals of the drill strings elements significantly, in the range of 15-35%, differs from the development of fatigue cracks on the air. It is established that under the influence of working loads the process of the corrosion-fatigue crack development in long-operated elements of drilling string is accelerated by more than 10% in the media of the potassium polymeric drilling mud than in the environment of drilling mud "Biocar".